2011
DOI: 10.1371/journal.pone.0028378
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and Adaptive Immune Responses against Mycobacterium tuberculosis Infection in Healthy and HIV Infected Individuals

Abstract: Glutathione (GSH), a tripeptide antioxidant, is essential for cellular homeostasis and plays a vital role in diverse cellular functions. Individuals who are infected with Human immuno deficiency virus (HIV) are known to be susceptible to Mycobacterium tuberculosis (M. tb) infection. We report that by enhancing GSH levels, T-cells are able to inhibit the growth of M. tb inside macrophages. In addition, those GSH-replenished T cell cultures produced increased levels of Interleukin-2 (IL-2), Interleukin-12 (IL-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(111 citation statements)
references
References 32 publications
(47 reference statements)
3
108
0
Order By: Relevance
“…Such observations are also confirmed with other antioxidants like manganese (II) mesotetrakis-(N-methylpyridinium-2-yl) porphyrin [27]. Further, glutathione is known to modulate the T cell mediated immune response in a manner that reduces the intracellular stability of the tuberculosis bacterium [28]. This fact is observed to be true for many other intracellular infection and so may be considered as a general phenomenon [29].…”
Section: Tuberculosis and The Antioxidant Paradoxsupporting
confidence: 52%
“…Such observations are also confirmed with other antioxidants like manganese (II) mesotetrakis-(N-methylpyridinium-2-yl) porphyrin [27]. Further, glutathione is known to modulate the T cell mediated immune response in a manner that reduces the intracellular stability of the tuberculosis bacterium [28]. This fact is observed to be true for many other intracellular infection and so may be considered as a general phenomenon [29].…”
Section: Tuberculosis and The Antioxidant Paradoxsupporting
confidence: 52%
“…However, interpretation of our results is tempered by the fact that we did not find an elevation of ROS levels in IFN-␥-primed Irgm1-deficient BMM compared with primed WT BMM. The NAC that was used in our studies is a commonly used direct ROS scavenger that also acts indirectly to quench ROS by inducing expression of glutathione (81)(82)(83). Nevertheless, some studies have found that NAC can cause effects in cells not related to ROS quenching, as a consequence of its reductive capacity and direct interaction with target proteins to modify their activities (84).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is elevated during HIV progression and is negatively correlated with GSH and also serves as a second messenger in oxidative stress [25, 60]. Also, studies have demonstrated that depleted GSH in HIV positive individuals [61] play a major role in the apoptosis of CD4 + T cells [62]. Furthermore, GSH levels in DC which maintains redox homeostasis and protecting DCs from oxidative stress are highly specialized in their ability to process and present exogenous antigen to CD4+ T helper cells and endogenous antigen to CD8+ T cells and accordingly influence the immune response by Th1 cytokine secretion [6365].…”
Section: Discussionmentioning
confidence: 99%